Next Generation Fiber-Reinforced Composites New Insights - Li, Longbiao; Pereira, António B.; Pereira, Alexandre L. (IntechOpen, 2023)
Composite materials have become an optimal option for a range of modern, industrial, clinical, and sports applications, offering a material with the desired properties and a limitless choice of building and composite levels. They possess noteworthy physical, thermal, electrical, and mechanical properties, in addition to being lightweight and cost-effective. This book focuses on the next generation of fiber-reinforced composites and adhesives, including recent advances in their development as well as their applications in numerous fields.